The Role of Product Information Quality and Streamer Credibility in Building Trust and Purchase Intention - Tiara Dinda Faizza; Ratna Roostika (Petra International Journal of Business Studies, 2024)
The rapid advancement of digital technology today. The presence of live streaming makes it one of the marketing strategies that allow us to share moments and sales in real time. Several factors influence the success of a marketing strategy using live streaming. This study analyzes Product Information Quality (PIQ), Streamer Information Quality (SIQ), and Streamer Credibility (SC) on Purchase Intention in the context of Shopee live-streaming. Trust becomes a mediating variable in consumer purchasing decisions. This research uses SOR theory with the focus of the research to understand and explain the quality of product and streamer information, as well as streamer credibility in influencing trust in online transactions. A quantitative approach was chosen to analyze the structural model by distributing a sample of 236 respondents, then processed with SEM-PLS. PLS analysis revealed that PIQ, SIQ, and SC positively and significantly influence Trust. Trust has a positive and significant effect on Purchase Intention. The research results are expected to enrich empirical findings related to the role of live streaming. The ability to develop trust should be considered in online marketing strategies because shopping is logical and emotional.